KNOWLEDGE, ATTITUDE AND PRACTICES REGARDING HUMAN PAPILLOMAVIRUS (HPV) VACCINATION AMONG ADOLESCENT GIRLS IN BIHAR AND EVALUATE THE FACTORS INFLUENCING IT- A CROSS SECTIONAL STUDY AT A TERTIARY CARE HOSPITAL. - Amrita; KUMARI, JAYA; SINHA, ARCHANA; PARWEEN, SADIA; SINGH, AKANKSHA; KUMARI, SUPRIYA (Student’s Journal of Health Research Africa, 2024)
Background Human Papillomavirus (HPV) is the causal factor for the development of carcinoma cervix in almost all cases. HPV vaccine is 100% effective against high-grade cervical lesions. Despite the availability of the HPV vaccine in India, the incidence of carcinoma cervix is likely to increase because of a lack of awareness of the HPV vaccine and less acceptability of the vaccine. Aim To assess the knowledge, attitude, and practices regarding HPV vaccination among adolescent girls in Bihar and evaluate the factors influencing it Material and methods A questionnaire-based cross-sectional study was done among 456 adolescent girls coming to the Outpatient Department. Questions related to knowledge about HPV infection and HPV vaccine were asked. Vaccination status and willingness to get vaccinated were also inquired of. Results The majority of patients (61.85%) were from rural areas, with the highest age group being 17-19 years (mean age 17.2 ± 2.7 years). Most participants were educated up to 12th grade, belonging to socioeconomic classes I and II. 7.68% hadn’t experienced menarche, 7.9% had a family history of malignancy, and 2.41% had sexual exposure. Awareness of cervical cancer was at 12.94%, with only 2.63% aware of the HPV vaccine. Healthcare workers were the primary source of information about the HPV vaccine. Only one participant had received the HPV vaccine. The majority (74.34%) were willing to get vaccinated if the vaccine was free, while uncertainty prevailed regarding parental willingness to pay (69.07% uncertain). Conclusion The awareness about HPV infection and vaccination is very low among adolescent girls in Bihar. The vaccine uptake is almost zero. Recommendation There is a need for increased sensitization among adolescent girls to improve HPV vaccine coverage.